FRI0309 The impact of belimumab and rituximab on health-related quality of life in patients with systemic lupus erythematosus. (12th June 2018) - Parodis, I.; Lopez Benavides, A.H.; Zickert, A.; Pettersson, S.; Möller, S.; Welin Henriksson, E.; Voss, A.; Gunnarsson, I.
Abstract : Background: Accumulating evidence supports an impaired health-related quality of life (HRQoL) in patients with systemic lupus erythematosus (SLE). The impact of modern therapeutic interventions on patients' perception of HRQoL has not been explored in depth. Objectives: The aim of this study was to investigate the effects of two biologic treatments – belimumab and rituximab – on SLE patients' HRQoL, fatigue and functional ability. Methods: Patients with SLE from the Karolinska University Hospital treated with either belimumab (n=34) or rituximab (n=35) were included. Data were collected prospectively at treatment initiation and at months 3, 6, 12 and 24; these included the Medical Outcome Study short form-36 (SF-36) version 2, functional assessment of chronic illness therapy (FACIT)-Fatigue scale version 4, EuroQol research foundation 5-dimension (EQ-5D) health questionnaire, and Stanford health assessment questionnaire disability index (HAQ-DI). Results: Substantial reductions compared to Swedish norms were observed across all SF-36 subscales at baseline (figure 1). SF-36 mental component summary scores were higher in patients who were on antimalarial agents (mean: 42.7; SD ±11.8; n=29) compared to patients who were not (mean: 34.0; SD ±14.7; n=32; p=0.019). Accordingly, patients who were on antimalarial agents performed better in SF-36 social functioning (mean: 63.7 versus 46.5; p=0.022) and mental health (mean: 68.7 versus 53.4; p=0.023) compared to patients who were not. Belimumab-treated patients reported gradual improvements in the SF-36 physical summary component (significant from month 12; p=0.023) and FACIT-Fatigue (significant by month 24; p=0.001), no changes in EQ-5D scores, and improvements in HAQ-DI by month 6 (p=0.014). Rituximab-treated patients reported rapid improvements in the SF-36 mental summary component and FACIT-Fatigue by month 3 (p=0.031 and p=0.007, respectively), which declined at month 12, as well as improvements in EQ-5D at month 6 (p=0.016) and HAQ-DI at month 3 (p=0.033), which were not maintained at later time points. Conclusions: HRQoL was considerably impaired in SLE patients compared to population-based norms at baseline, and was not fully compensated during follow-up. Patients' perceptions of HRQoL showed treatment-specific patterns over time, and could prove useful when evaluating the effects of biologics in SLE. Early evaluation of belimumab might underestimate improvements in HRQoL and fatigue. In severe SLE, antimalarial agents may have favourable effects on mental HRQoL aspects. Disclosure of Interest: None declared